Investigating the nexus between Mobile Apps Adoption and Privacy Concerns among Users: An Empirical Analysis from Ghana - Owusu, Acheampong; Taana, Ivy Hawah; Bakare, Akeem Soladoye; Abdurrahaman, Daha Tijjani; Broni Jnr, Frederick Edem (Technium Social Sciences Journal, 2020)
There has been a proliferation of Mobile Phones Applications commonly referred to as Mobile Apps lately due to the advancement of technology. These Mobile Apps are used for a myriad of tasks ranging from Mobile Commerce (m-commerce), healthcare, learning, social media, among others. However, with this spread of the Mobile Apps comes the issues of privacy concerns. This study, therefore, seeks to investigate why users continue to use the Mobile Apps despite the privacy concerns and what measures they have put in place to mitigate this menace. Through the Antecedents, Privacy, Concerns, and Outcome (APCO) model, the study developed a research model that was hypothesized and evaluated with 316 respondents from a tertiary institution. The data was analyzed through the partial least squares structural equation model (PLS-SEM). The results indicate that whilst antecedent variable Gender influences Privacy Concern, Experience on the other hand does not. Also, Enjoyment, Privacy Risk, and Trust influence Usage Continuance Intention. Also, Application Popularity influences Change Privacy Settings. Again, Privacy Concern influence Privacy Risk but does not influence Trust. Moreover, Enjoyment, Privacy Risk, and Trust do not influence Change Privacy Settings. This study has given the researchers insights as to why users continue to use Mobile Apps despite the Privacy Concerns that have been raised in the literature. Other implications for theory, policy, and practice are also discussed.